Motivação para aprender em estudantes do Ensino Básico: uma revisão de pesquisas brasileiras de 2018 a 2022 - Silva, Patrick Gonçalves Toledo da (2024)
Motivation, according to various authors, is one of the fundamental pillars that drive human action, decisively influencing how individuals engage in various activities, and this principle is also relevant in the context of learning and education. The national research landscape is actively evolving in this regard. With this in mind, the focus of this study was to conduct a literature review on scientific production related to motivation for learning in the Brazilian context. The research was carried out on the Scielo platform, covering the period from 2018 to 2022. Seven relevant articles on motivation for learning were selected for analysis. This evaluation resulted in the identification of a specific thematic category: Empirical articles with tests and scales. The results indicated that the overwhelming majority of students demonstrated intrinsic motivation, emphasizing the importance of family support, psychological well-being, and self-efficacy in the development of motivation for learning